Affectfullness as the basis for the (re)formulation of the teacher´s professional identity - Loos-Sant'Ana, Helga; Sant'Ana-Loos, René Simonato; Oliveira, Clésnia de (International Journal for Innovation Education and Research, 2020)
‘Affectfullness’ is called the way of life defended by Theoretical System of Affectfullness (TSA) in which the interactions we experience in the world can become rich and meaningful. Seen in these terms, it may be understood as a method that provides parameters for analyzing our experiences and investing in our full development as human beings. As of this approach, the teaching and learning activities should also be seen from a broader perspective, since they have a relevant role in the developmental path of our species. Therefore, it is argued that in scholastic institutions, the teacher – the person in charge of ‘teaching’- needs to experience opportunities and perspectives of self-development which happens through participation in healthy interactions and appropriate conditions to carry out their work of transmitting the input of knowledge produced by humanity from generation to generation. However, unfortunately we have noticed that a large number of elementary school teachers in Brazil do not perceive themselves inserted in a context full of development possibilities, both of themselves and of their own students. Teachers experience discomfort and anxieties, which in turn result in disenchantment with their teaching activities. This paper aims to explore, based on the literature researched, some of the difficulties lived by performing teachers which were organized in seven sections that indicate how the integrity of the ‘teaching profession’ has negatively been affected. Then, it promoted a dialogue with the Theoretical System of Affectfullness (TSA) in order to elicit reflections, which contribute to the teachers arouse an “affectively expanded look” on the dimension of their daily work and their professional identity, becoming able to positively affect their work environment and help modify this reality for better.